Crystal structure of cyclo[tetraiodido-bis{μ2-1-[(benzotriazol-1-yl)methyl]-1-H-1,3-(2-isopropyl-imidazol)-k2N:N}dicadmiun(II)], C26H30N10Cd2I4 - Yang Hai-Yan; Wang Hong-Fang; Li Hui; Li Ying-Hua; Zhao Yao-Min (Zeitschrift für Kristallographie - New Crystal Structures)
C26H30N10I4Cd2, monoclinic, P21/n (no. 14), a = 8.1164(10) Å, b = 15.9401(18) Å, c = 13.5531(17) Å, β = 96.067(4)∘$96.067{(4)}^{° }$, V = 1743.6(4) Å3, Z = 2, Rgt${R}_{gt}$(F) = 0.0394, ωRref(F2) = 0.1088, T = 273 K.